The Simulation of Covid-19 Droplet Transmission with Hamiltonian Monte Carlo Method - Mutia Delina; Irsyad Tio Majid; Ahmad Fauzan (INDONESIAN JOURNAL OF APPLIED PHYSICS, 2022)
Corona Virus 2019 (COVID-19) pandemic has impacted every sector in the world. This virus spread through the droplet and infected healthy people. The typical of virus transmission is through droplets from coughing and sneezing. This study developed a simulation to model a virus spread just after the infected was coughed or sneezed. In the simulation, humidity, wind velocity, and temperature were considered.  The simulation was conducted with Hamiltonian Monte Carlo, where was set a random initial velocity and angle for every 200 droplets with 500 iterations of each. The transmission data was derived from three groups: the age of 15 to 30 years old, 31 to 50 years old, 51 to 68 years old. At the age of 12 to 30 years, the droplet range and height were 3.13 meters and -0.77 meters. At the age of 31 to 50 years old, the droplet range and height were 3.22 meters and -0.83 meters. At the age of 51 to 68, the droplets range and height were 2.82 meters and -0.58 meters. The highest droplet range was from the age of 31 to 50 years old. Therefore, the age of 31 to 50 years old or the productive age was considerable with the highest risk in the droplet transmission and virus spread. This study can be adopted to consider the effective prevention in controlling the virus outbreaks.